Assessment system for mathematics – G - Ong, Ting Swee. (2013)
Education in Singapore has been a very competitive system. Parents and education experts believe that assessment books can act as a supplement to their children studies. Currently in the market, one can rarely find an assessment book that is not hardcopy. These books normally have limited questions and do not have the flexibility to change the question, there may be a time where the person finishes all the question of the whole book and wanted to practice more. This limits the education trainers on how they can deepen their assessment on their student’s knowledge.